Efeito da lavagem peritoneal com bupivacaína na sobrevida de ratos com peritonite fecal - Brocco, Marcos Célio; Paulo, Danilo Nagib Salomão; Baptista, João Florêncio de Abreu; Carraretto, Antônio Roberto [UNESP]; Ferrari, Thiago Antunes; De Azevedo, Thiago Caetano V.; Da Silva, Alcino Lázaro (Elsevier, 2008)
BACKGROUND AND OBJECTIVES: Based on the knowledge of the anti-inflammatory and anti-bacterial actions of local anesthetics (LA), the objective of this study was to determine the effects of peritoneal lavage with bupivacaine on survival of mice with fecal peritonitis. METHODS: Forty-eight Wistar mice, weighing between 300 and 330 g (311.45 ± 9.67 g), undergoing laparotomy 6 hours after induction of peritonitis were randomly divided in 4 groups: 1 - Control, without treatment (n = 12); 2 - Drying of the abdominal cavity (n = 12); 3 - Lavage with 3 mL NS and posterior drying of the abdominal cavity (n = 12); and 4 - Lavage with 8 mg.kg -1 (± 0.5 mL) of 0.5% bupivacaine added to 2.5 mL of NS followed by drying out of the abdominal cavity (n = 12). Animals that died underwent necropsy and the time of death was recorded. Surviving animals were killed on the 11 th postoperative day and underwent necropsy. RESULTS: Group 1 presented a 100% mortality rate in 52 hours, 100% mortality rate in Group 2 in 126 hours, and Group 3 presented a 50% mortality rate in 50 hours. Animals in Group 4 survived. Survival on the 11 th day was greater in groups 3 and 4 than in Groups 1 and 2 (p < 0.001) and greater in Group 4 than in Group 3 (p < 0.01). CONCLUSIONS: Peritoneal lavage with a solution of bupivacaine diluted in NS was effective in preventing death for 11 days in 100% of animals with fecal peritonitis. © Sociedade Brasileira de Anestesiologia, 2008.
Effects of peritoneal lavage with bupivacaine on survival of mice with fecal peritonitis
Keywords: Anesthetic, local: Bupivacaine; Animals: Mice; Complications, infection: Peritonitis; amikacin; aminoglycoside antibiotic agent; amoxicillin plus clavulanic acid; ampicillin; antibiotic agent; bupivacaine; cefazolin; ceftriaxone; cephalosporin derivative; ciprofloxacin; clindamycin; cotrimoxazole; erythromycin; gatifloxacin; gentamicin; ketamine; levofloxacin; lidocaine; linezolid; local anesthetic agent; nitrofurantoin; norfloxacin; oxacillin; penicillin derivative; quinoline derived antiinfective agent; rifampicin; ropivacaine; sultamicillin; unindexed drug; vancomycin; animal experiment; animal model; antibacterial activity; antibiotic sensitivity; antiinflammatory activity; controlled study; drug effect; feces; Gram negative bacterium; Gram positive bacterium; immune response; laparotomy; mortality; mouse; nonhuman; peritoneal cavity; peritoneum lavage; peritonitis; sepsis; survival rate